The role of informal learning spaces in enhancing student engagement with mathematical sciences. Issue 4 (19th May 2017) - Waldock, Jeff; Rowlett, Peter; Cornock, Claire; Robinson, Mike; Bartholomew, Hannah
ABSTRACT: By helping create a shared, supportive, learning community, the creative use of custom-designed spaces outside the classroom has a major impact on student engagement. The intention is to create spaces that promote peer interaction within and across year groups, encourage closer working relationships between staff and students and support specific coursework activities – particularly group work. Such spaces make better use of time since students are motivated to stay and work during long gaps in their timetable, can provide a sense of 'home' within the institution and can lead to a cohesive community of practice. In this paper, we describe how this has been achieved and currently delivered in Mathematics at Sheffield Hallam University and provide some detailed analysis of the student usage of the space.